Pemilihan Destinasi Berkemah: Suatu Analisis Relevansi Determinan - Oce Ridwanudin; Andreas Suwandi; Silvi Sintia Andini (Tourism Scientific Journal, 2022)
One of the industries that were highly impacted by Covid 19 pandemic is tourism. This requires adaptive measures and recovery strategies in order to survive. Among tourism activities that were considered attractive during the pandemic is camping, therefore camping destination managers are required to increase their competitive advantage to win the competition. The purpose of this study is twofold; first is to obtain findings on which attributes of camping are considered most important and second is to obtain findings on which camping attributes give the most experience to the tourists. The method employs in this study is determinant-relevance analysis while the object is three camping sites in Bandung Regency that is Ranca Upas, Batu Kuda, and Ranca Cangkuang. The result of the study shows that camping atmosphere is the most important attribute of camping site choice and is the attribute that gives the most experience to the tourists. Thus, managers need to highlight on the attribute in their promotion activities to gain more visits.